STRATEGI KEBERLANJUTAN USAHA MELALUI PENDAMPINGAN PENGELOLAAN KEUANGAN PADA USAHA MIKRO BU EDY BAKERY - Meilan, Ria (Jurnal Pengabdian Masyarakat dan Lingkungan, 2024)
The existence and sustainability of MSMEs cannot be separated from how these MSMEs manage their business. Financial management has now become a crucial problem for MSMEs. A micro business's existence is not only carried out by business actors but also requires support from parties who can contribute to assisting the micro business to be better and develop over time. The aim of this community service activity is as a form of implementing the tridharma of higher education to provide assistance to partners regarding financial management by compiling simple bookkeeping. Mitra's location is located in Kunir Lor Village, Lumajang Regency with the partner's business focus being in the processed food or bakery sector. Bu Edy Bakery's community service partners are limited in understanding financial management and presenting business financial reports. Socialization and assistance activities for financial management with simple bookkeeping are designed and arranged as the most feasible and easy to carry out, adapting to partners' business activities. Apart from that, the use of technology in the form of the Lamikro application is used to make it easier for partners to carry out accounting records. The benefits of this community service activity increase partners' understanding as business actors about the benefits of bookkeeping so that they can record every financial transaction that occurs so that they can separate business finances from personal finances.